2012
DOI: 10.1021/jp210439n
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of Pluronic Micelles by Di-Methylated β-Cyclodextrin Is Not Due to Polypseudorotaxane Formation

Abstract: Spectroscopic measurements (uv/vis absorbance and fluorescence) and time-resolved small-angle neutron scattering experiments (TR-SANS) were used to follow the breakdown of Pluronic micelles by heptakis(2,6-di-O-methyl)-β-cyclodextrin (DIMEB) over time in order to elucidate the mechanism of micellar rupture, generally attributed to polypseudotorotaxane (PR) formation between the cyclodextrin and the central hydrophobic PPO block. The spectroscopic measurements with two different probes (methyl orange and nile r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 33 publications
4
48
0
Order By: Relevance
“…Both the magnitude of this drop and the speed at which it takes place increases with increasing DIMEB concentration and it is particularly drastic at 3% DIMEB, irrespectively of the molar mass of the block copolymer (SI, Figure S3). This effect of methylated CDs on shifting the unimer-micelle equilibrium has been reported for linear block copolymers 51,52 and other surfactants, like TPGS. 44 For example, using TR-SANS, it has been observed that Pluronic P85, P123 and F127 undergo fast micellar rupture with DIMEB, which has been ascribed to the existence of weak interactions between the PPO methyl groups and those of the primary and secondary rims of the macrocycle, leading to increased solubility.…”
Section: Threading At Short Times: Kinetics Of Demicellisationsupporting
confidence: 69%
“…Both the magnitude of this drop and the speed at which it takes place increases with increasing DIMEB concentration and it is particularly drastic at 3% DIMEB, irrespectively of the molar mass of the block copolymer (SI, Figure S3). This effect of methylated CDs on shifting the unimer-micelle equilibrium has been reported for linear block copolymers 51,52 and other surfactants, like TPGS. 44 For example, using TR-SANS, it has been observed that Pluronic P85, P123 and F127 undergo fast micellar rupture with DIMEB, which has been ascribed to the existence of weak interactions between the PPO methyl groups and those of the primary and secondary rims of the macrocycle, leading to increased solubility.…”
Section: Threading At Short Times: Kinetics Of Demicellisationsupporting
confidence: 69%
“…32,33 The substitution of the hydroxyl groups on the rims of the CD strongly modifies the aggregation behavior of the Pluronic micelles, depending on the specific nature of the substituents, [34][35][36] and the kinetics and mechanisms of the formation of the PPRs have been studied. [37][38][39] Specifically, the PRs formed with 2-hydroxypropyl β-CD and Pluronic have shown promise in the biomedical field for the treatment of Niemann-Pick disease. [40][41][42] Another type of block-copolymers of interest as guests for cyclodextrins is poloxamines, also known by their commercial name of Tetronic® (BASF).…”
Section: Introductionmentioning
confidence: 99%
“…A similar template method was used by Bleta et al for synthesizing mesoporous alumina with controlled pore size, by taking advantage of the micellar co‐assembly of a triblock copolymer and methylated cyclodextrin. Valero et al concluded that methylated β‐cyclodextrins do not form pseudorotaxanes with PEO–PPO–PEO. However, Bleta et al found that the copolymer PEO 20 PPO 70 PEO 20 (Pluronic P123, M w = 5800 g/mol) and a randomly methylated β‐cyclodextrin (denoted by RAMEB) co‐assembled in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%